2021
DOI: 10.1093/bjs/znaa075
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative infection and mortality following elective surgery in the International Surgical Outcomes Study (ISOS)

Abstract: Background Postoperative infection is one of the most frequent and important complications after surgery. The epidemiology of infection following elective surgery remains poorly described. Methods This was a prospective analysis of the International Surgical Outcomes Study (ISOS) describing infection by 30 days after elective surgery. Associations between postoperative infection (primary outcome) and baseline demographic, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…38 The overall rate of surgical site infection in the reported trials is comparable to the incidence of 5e10% reported in recent international epidemiological studies. 4,7,39,26 In a meta-regression including the year of the study, we found minimal change in the rate of surgical site infection, or influence of liberal antimicrobial prophylaxis. Whereas the effectiveness of infection control measures have improved over time, patient risk factors (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…38 The overall rate of surgical site infection in the reported trials is comparable to the incidence of 5e10% reported in recent international epidemiological studies. 4,7,39,26 In a meta-regression including the year of the study, we found minimal change in the rate of surgical site infection, or influence of liberal antimicrobial prophylaxis. Whereas the effectiveness of infection control measures have improved over time, patient risk factors (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…Los factores asociados a una mayor incidencia de infección en los análisis ajustados fueron: edad, sexo masculino, grado ASA, enfermedad comórbida, anemia preoperatoria, técnica anestésica, categoría quirúrgica, gravedad quirúrgica y cirugía oncológica. La infección aumentó significativamente el riesgo de muerte (odds ratio 4,68; Intervalo de Confianza del 95%: 3,39 a 6,47; p < 0,001) y la duración de la estancia hospitalaria en una media de 6,45 días [29]…”
Section: Infección De La Herida Quirúrgicaunclassified
“…As the life expectancy of the population increases, a higher number of surgical interventions are now performed in patients with more comorbidities and more complex procedures will be done [2]. In the last 15 years, cohort studies in different countries and regions have confirmed that the overall surgical mortality is about 4%, and the high-risk population comprises 20% of the surgical patients but contributes to higher rates of complications and mortality and to 80% of costs [3][4][5].…”
Section: Introductionmentioning
confidence: 99%